Pre-Hypertension and Hypertension in A Private Tertiary Care Centre in Kancheepuram District Of Tamil Nadu, India and Their Association with Risk Factors of Cardiovascular Diseases - Govindan, Rekha; Kumar, V Rahul; Singh, Rana Ranvijay; Dolly; Shaikh Gouse Basha, Imran; Kumar, Vikas (National Journal of Community Medicine, 2013)
Background: The proportion of hypertension in India as reported by various literatures has been on an increasing trend for the last three decades. The present study was carried out to determine the proportion of hypertension, its associated risk factors as well as to increase the awareness on importance of life style modifications among people visiting a rural hospital. Methodology: Adults of age 18 years above, residing in and around Paiyanoor and visiting Vinayaka Mission Chennai hospital, Paiyanoor, Kancheepuram District, Tamilnadu for a period of two month was invited to be enrolled for the study. Hypertension was diagnosed as per the seventh report of the joint national committee on prevention, detection, evaluation and treatment of high blood pressure. Biochemical estimation of serum triglycerides, cholesterol, HDL, LDL and VLDL was carried out. Statistical differences were obtained by one-way analysis of variance (ANOVA) for continuous variables and chi-square test for categorical variables. P values < 0.05 were considered to be statistically significant. Results: The study subjects were grouped into normotensive, pre-hypertensive and hypertensive. 67.64% of the study subjects are hypertensive (p< 0.01) with a mean blood pressure of 145.13±12.52 / 93.61±9.68mmHg, SBP & DBP respectively. Significant differences of LDL and cholesterol levels are noted among the pre-hypertensive and hypertensive subjects when compared with the normotensive subjects. Conclusion: A higher proportion of pre-hypertension and hypertension and significant differences in terms of age, occupational activity, cholesterol and LDL was observed among the study subjects. The present study supports the increasing trend in the rural communities of India which are under epidemiological transition.